2022
DOI: 10.1111/ajt.16990
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of a viral neutralizing humoral response after a third dose of COVID-19 mRNA vaccine

Abstract: Kidney transplant recipients (KTRs) have reduced ability to mount adequate antibody response after two doses of the COVID‐19 mRNA vaccine. French health authorities have allowed a third booster dose (D3) for KTRs, but their response is heterogeneous and tools able to discriminate the responders are lacking. Anti‐RBD IgG titers (chemiluminescence immunoassay), spike‐specific cellular responses (IFN‐γ‐releasing assay, IGRA), and in vitro serum neutralization of the virus (the best available correlate of protecti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 44 publications
(106 reference statements)
2
14
0
Order By: Relevance
“…Given the poor rates of immunologic response, a three-dose regimen for immunocompromised individuals has been implemented, and was reported to be associated with a marked improvement in immunologic response in KT recipients [ 33 36 ]. In a French cohort of 78 adult KT recipients, SARS-COV-2 antibodies were detected in 40% of patients following the second dose compared to 68% following the third dose [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the poor rates of immunologic response, a three-dose regimen for immunocompromised individuals has been implemented, and was reported to be associated with a marked improvement in immunologic response in KT recipients [ 33 36 ]. In a French cohort of 78 adult KT recipients, SARS-COV-2 antibodies were detected in 40% of patients following the second dose compared to 68% following the third dose [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, in two studies that used flow cytometry, S-protein-reactive T cells were detected in 90% and 95%, respectively 137 , 139 . Importantly, detectable levels of anti-RBD IgG antibodies and S-protein-reactive CD4 + T cells were predictive of a high response to the third primary vaccine dose 131 . By contrast, <10% of patients with failed seroconversion and negative IFNγ-release assay responded to a third dose 131 .…”
Section: Strategies To Improve Vaccination Responsesmentioning
confidence: 96%
“… 16 In a French cohort study, lower posttransplant duration and high‐maintenance immunosuppression were found to be unfavorable predictors for seroconversion in KT recipients. 22 These parameters could be used to create a COVID‐19 immunization plan customized by individual immune status. The strategy of temporarily pausing immunosuppressant use has been proposed; however, allograft rejection is a barrier to implementing this practice, especially for those with high a immunologic risk or recent transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…16 In a French cohort study, lower posttransplant duration and highmaintenance immunosuppression were found to be unfavorable predictors for seroconversion in KT recipients. 22 vaccine types as a booster dose. 17 Some of our participants experienced more pain on the injected side after receiving the mRNA vaccine compared with the viral vector vaccine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation